Cell Tropism and Pathogenesis of Measles Virus in Monkeys - Kato, Sei-ich; Nagata, Kyosuke; Takeuchi, Kaoru (Frontiers in Microbiology, 2012)
Measles virus (MV) is an enveloped negative strand RNA virus belonging to the family of Paramyxoviridae, genus Morbillivirus, and causes one of the most contagious diseases in humans. Experimentally infected non-human primates are used as animal models for studies of the pathogenesis of human measles. We established a reverse genetics system based on a highly pathogenic wild-type MV (IC-B strain). Infection of monkeys with recombinant MV strains generated by reverse genetics enabled analysis of the molecular basis of MV pathogenesis. In addition, recombinant wild-type MV strains expressing enhanced green fluorescent protein enable visual tracking of MV-infected cells in vitro and in vivo. To date, 3 different molecules have been identified as receptors for MV. Signaling lymphocyte activation molecule (SLAM, also called CD150), expressed on immune cells, is a major receptor for MV. CD46, ubiquitously expressed in all nucleated cells in humans and monkeys, is a receptor for vaccine and laboratory strains of MV. The newly identified nectin-4 (also called PVRL4) is an epithelial cell receptor for MV. The impact of MV receptor usage in vivo on disease outcomes is now under investigation.